2020
DOI: 10.1080/10357823.2020.1849026
|View full text |Cite
|
Sign up to set email alerts
|

Body Modification in East Asia: History and Debates

Abstract: This article outlines the long-term historical development of body modification in East (Northeast and Southeast) Asia, from the intentionally transformative practices of prehistory, such as tattooing and tooth blackening, to the "naturalistic" practices of the 20 th century, such as cosmetic surgery, which aim to leave no visible evidence of change. Attention is also paid to the recent postmodern revival of transformative body fashions. Asian developments are discussed in global context, and comparative inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…To pursue beauty is human nature. However, people have a different opinion of beauty; many people from East Asian countries want white and flawless skin [ 22 ]. The World Health Organization (WHO) survey found that up to 40% of women in China, Malaysia, Philippines, and South Korea have experience in using whitening products [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To pursue beauty is human nature. However, people have a different opinion of beauty; many people from East Asian countries want white and flawless skin [ 22 ]. The World Health Organization (WHO) survey found that up to 40% of women in China, Malaysia, Philippines, and South Korea have experience in using whitening products [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 Culturally speaking, tattooing is synonymous with talismanic symbolic and status markers; but maybe the phenomenon has received actually global significance. 32 The overall consideration of tattoos as being proportionally connected with anti-social tendencies, and their high prevalence in high-risk groups (for example, prisoners), will add further queries and concerns while considering these issues. 33…”
Section: Theoretical Approaches To the Issuementioning
confidence: 99%